Association Between A-Waves and Outcome in Pediatric Guillain-Barré Syndrome - Jin, Mei; Liu, Jing; Zhao, Ziwei; Geng, Wenjin; Sun, Suzhen (Frontiers in Neurology, 2022)
Introduction: To examine the importance of abundant A-waves in electrophysiological classification and prognosis of paediatric Guillain-Barré syndrome. Methods: Single-center, retrospective study enrolling 65 children patients, aged 16 years and younger, with clinically diagnosed GBS between 2013 to 2020. Hughes grade was used to assess functional disability at nadir, 1 month and 6 months after symptom onset. Patients were divided into 2 groups according to the presence of abundant A-waves. Clinical features and prognosis between the 2 groups were compared. Results: The distal motor latency of median nerve in GBS patients with A-waves (9.18ms) was more prolonged than that of GBS patients without A-waves (4.1ms). Electrophysiological variant of these two groups were also statistically different (p = 0.006).The short-term prognosis of AIDP patients with A-waves was worse than AIDP patients without A-waves (p = 0.025), univariable logistic regression analysis showed statistical significant (OR:5.844,95% CI 1.118-30.553; p = 0.036). Conclusion: A-waves were strongly associated with demyelination and poor short-term prognosis of AIDP in children. We proposed an electrophysiological marker for early prediction of outcome in the AIDP subtype of GBS, applicable for clinical practice and future treatment administration.